Atmospheric Brown Carbon: Sources, Optical Properties, and Chromophore Composition - Ashmeet Kaur Alang; Shankar G. Aggarwal (Aerosol and Air Quality Research)
Abstract Brown carbon (BrC) constitutes a significant portion of organic carbon (OC) and exerts a substantial influence on air quality, atmospheric chemical processes, and the impact on climate dynamics. The intricate chemistry of BrC arises from multiple mechanisms and source types, yielding a wide spectrum of spectral properties. Consequently, identifying representative chromophore species to develop reference material is crucial to capture the full diversity of BrC found in the atmosphere and to ensure its precise determination. This also emphasizes the need for a more comprehensive measurement method to link BrC’s optical traits with its chemical composition. One of the objectives of this review is to evaluate the existing level of understanding concerning the molecular compositions of BrC compounds by analyzing recent field and laboratory data. This paper revises and expands a part of the prior database containing critical assessments of the primary and secondary sources, photochemistry of multi-phase chemical reactions involving BrC, potential candidate BrC chromophores, and recent studies on optical properties of BrC in the cryosphere, to draw lessons from recent advances that lead to improved BrC representation in the atmosphere.